A close look at current γδ T-cell immunotherapy - Ma, Ling; Feng, Yanmin; Zhou, Zishan (Frontiers in Immunology, 2023)
Due to their antitumor and MHC-independent capacities, γδ T cells have gained popularity in adoptive T cell immunotherapy in recent years. However, many unknowns still exist regarding γδ T cells, and not much clinical data has been conducted. Therefore, this review aims to cover all the main features of the applications of γδ T cells in different aspects and provide a systematic view of current γδ T cell immunotherapy. Specifically, this review will focus on how γδ T cells were performed in treating cancers in clinics, the γδ T cell clinical trials that have been conducted to date, and the role of γδ T cells in the industry.